2015
DOI: 10.1111/anu.12278
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary glucose and starch levels on the growth, haematological indices and hepatic hexokinase and glucokinase mRNA expression of juvenile mirror carp (Cyprinus carpio)

Abstract: The effect of the different dietary carbohydrate types and levels on growth performance, haematological indices and hepatic hexokinase (HK) and glucokinase (GK) genes expression involved in control of glucose metabolism, was studied in juvenile mirror carp (Cyprinus carpio). Two carbohydrates (glucose and starch) diets with two levels (250 and 500 g kg À1 ) were fed to triplicate groups of 35 fish for 60 days. The best weight gain rate and specific growth rate were observed in fish fed with 250 g kg À1 glucose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 57 publications
(63 reference statements)
7
17
0
Order By: Relevance
“…Other influential factors include differences in physiology, gastrointestinal anatomy and hormonal responses (Hung, Fynn‐Aikins, Lutes, & Xu, ). Comparing the studies is problematic in addition to the varying abilities of different fish species in glucose or starch utilization, dietary formulation, water temperature, feeding strategies and fish body size (Lee, Kim, & Lall, ; Li et al, ). Fish generally exhibit a limited capacity to metabolize extra available glucose, thereby resulting in postprandial hyperglycaemia that lasts for many hours (Small & Soares, ).…”
Section: Discussionmentioning
confidence: 99%
“…Other influential factors include differences in physiology, gastrointestinal anatomy and hormonal responses (Hung, Fynn‐Aikins, Lutes, & Xu, ). Comparing the studies is problematic in addition to the varying abilities of different fish species in glucose or starch utilization, dietary formulation, water temperature, feeding strategies and fish body size (Lee, Kim, & Lall, ; Li et al, ). Fish generally exhibit a limited capacity to metabolize extra available glucose, thereby resulting in postprandial hyperglycaemia that lasts for many hours (Small & Soares, ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the present study aimed to decrease dietary protein content via substitution of potato starch, while previous studies did not change the dietary protein content by substituting a digestible carbohydrate source (corn starch) by an indigestible source (cellulose). It is well established that carbohydrate level and source show effects on growth, feed utilization and metabolism of finfish, and that these are attributable to the interaction between proteins and lipids [8,16].…”
Section: Discussionmentioning
confidence: 99%
“…Starch is a relatively complex polysaccharide; its dietary inclusion is variable, although its use is feasible in finfish diets, especially in species with omnivorous habits [7], such as common carp (Cyprinus carpio, Linnaeus 1758). Different authors reported on the use of carbohydrates (starches) with excellent results for growth and survival of freshwater carp [8]. In this context, it has been suggested that carbohydrates should not exceed 15% of the dietary dry weight for fish, because the excess of these compounds results in stunting and reduced digestibility of other nutrients [6,9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…An excess proportion of carbohydrates in their diet causes metabolic syndrome, including decreased growth performance [5], persistent hyperglycemia [6], and excess lipid deposition [7,8]. The glucose regulation mechanism in fish has been discussed in numerous studies; however, until now, most metabolic genes related to carbohydrate/glucose utilization have been found to be conserved in vertebrates [9].…”
Section: Introductionmentioning
confidence: 99%